Metallaphotoredox catalysis with organic dyes. Issue 16 (6th April 2021) - Gualandi, Andrea; Anselmi, Michele; Calogero, Francesco; Potenti, Simone; Bassan, Elena; Ceroni, Paola; Cozzi, Pier Giorgio
Abstract : Here…comes the fun…Combination of metals and organic photocatalysts allows the practical invention of new methodologies! Abstract : The use of organic dyes to promote organic reactions by photoredox catalysis is continuously expanding and was recently reviewed by Nicewicz. The synthesis of new dyes, their application in flow photoredox reactions, and their use in stereoselective and multicomponent transformations have considerably expanded the repertoire of application of organic dyes in photoredox mediated reactions. The low costs of these dyes, their tailored synthesis and availability in combination with the development of new concepts and careful catalytic cycle design (made possible by the application of fine theoretical investigations and deep understanding) are guiding the widespread application of organic dyes in the metallaphotoredox catalysis area. Developments and recent applications of different metal catalyzed processes mediated by organic dyes are covered by this review.